Motor activity: Motor control and learning - Wiemeyer, J. (Modelling and simulation in sport and exercise, 2020)
In the first chapter, addressing motor activity, Wiemeyer gives an introduction to the concepts and techniques of motor control and motor learning, where "motor control denotes the capability to successfully perform goal-directed movements, whereas motor learning is defined as an experience-based process leading to a more or less permanent change of perception and action". The perspectives of modelling stretch from biomechanical and neurophysiologic to psychological approaches, generating a great diversity of model types. In particular, Wiemeyer discusses different types of motor activity modelling, thereby giving an informative introduction to the practical meaning of the underlying modelling paradigms.